2007
DOI: 10.1074/jbc.m701396200
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide-1-phosphate Binds Group IVA Cytosolic Phospholipase a2 via a Novel Site in the C2 Domain

Abstract: Previously, ceramide-1-phosphate (C1P) was demonstrated to be a potent and specific activator of group IV cytosolic phospholipase A 2 ␣ (cPLA 2 ␣) via interaction with the C2 domain. In this study, we hypothesized that the specific interaction site for C1P was localized to the cationic ␤-groove (Arg 57 , Lys 58 , Arg 59 ) of the C2 domain of cPLA 2 ␣. In this regard, mutants of this region of cPLA 2 ␣ were generated (R57A/K58A/R59A, R57A/R59A, K58A/R59A, R57A/K58A, R57A, K58A, and R59A) and examined for C1P af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 49 publications
5
142
0
1
Order By: Relevance
“…Cer-1-P interacts with the cationic ␤-groove (Arg-57, Lys-58, and Arg-59) of the C2 domain of cPLA 2 ␣. This enhances interaction with membranes and lowers the EC 50 for Ca 2ϩ down to 31 nM, resulting in increased and catalytic activity in vitro (22,24). Recently, it has been described that CERK is required for cPLA 2 ␣ activation and translocation to the Golgi in response to Ca 2ϩ increases in the cell (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cer-1-P interacts with the cationic ␤-groove (Arg-57, Lys-58, and Arg-59) of the C2 domain of cPLA 2 ␣. This enhances interaction with membranes and lowers the EC 50 for Ca 2ϩ down to 31 nM, resulting in increased and catalytic activity in vitro (22,24). Recently, it has been described that CERK is required for cPLA 2 ␣ activation and translocation to the Golgi in response to Ca 2ϩ increases in the cell (25).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the single mutation D43N in the C2 domain of the enzyme, which abrogates its Ca 2ϩ binding capacity, does not affect activity in response to FBS. Several reports have established the dispensability of Ca 2ϩ rises in terms of full enzyme activation in vivo (13, 16 -19) while putting forward the requirement of the signaling lipids PtdIns-4,5-P 2 (17,20,21,34) and Cer-1-P to allow interaction with membranes (22)(23)(24)(25). The D43N mutation in cPLA 2 ␣ renders the enzyme refractory to physiological Ca 2ϩ concentrations (31), but it is fully active on PtdIns-4,5-P 2 -containing micelles (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we have shown that the membrane-associated phosphatidylinositol 4,5-bisphosphate can bind to the "lysine pocket" of GIVA PLA 2 with high affinity and specificity to activate the GIVA PLA 2 independent of Ca 2ϩ (16,17). Another membraneassociated activator, ceramide 1-phosphate, has been shown to bind to the cation groove of the C2 domain to activate GIVA PLA 2 in a Ca 2ϩ -dependent manner (18,19). Calcium binding is crucial for GIVA PLA 2 activation.…”
mentioning
confidence: 99%
“…ii) On Ca 2+ activation, the C2 domain of cytosolic phospholipase A2 (cPLA2) targets specifically to internal membranes, thereby initiating inflammation (14). Targeting specificity requires the neutral lipid phosphatidylcholine (PC) and the anionic lipid ceramide-1-phosphate (C1P) (10,15). PC binds to charged, polar and hydrophobic side chains near the Ca 2+ site (16,17), whereas C1P binds a separate basic cluster (Arg 2 -Lys) (15).…”
mentioning
confidence: 99%